Relación entre Síndrome de Burnout y Satisfacción-Insatisfacción Laboral en los Profesionales de Enfermería del Servicio Nº 6 Hospital Nacional Guillermo Almenara Irigoyen, Lima (Perú) 2009. - Mary Luz Solórzano Aparicio (2019)
Purpose: To determine the relationship there is between the Burnout Syndrome and the work satisfactionnon-satisfaction among nursing professionals from the “Guillermo Almenara Irigoyen” General Hospital,Service Nº 6. Methodology: The present research was descriptive, correlational, cross-sectional study. 44nurses from Section No. 6 were surveyed from the Geriatric, General Medicine, and Psychiatric Units.The Maslach Burnout Inventory (MBI) questionnaire and the Warr Cook and Wall Work Satisfaction Scalequestionnaire were applied. Results: The values obtained were of 11.29 ± 3.41 in emotional burnout; 4.69 ±2.13 of depersonalization; and, 37.4 ± 2.35 of personal performance. A media of 44.04 ± 1.41 was obtained forintrinsic satisfaction, 47.89 ± 1.77 for the extrinsic satisfaction, and 91.93 ± 2.35 in the overall. Conclusions:The sample observed gave enough evidence to determine that there is no relationship between the BurnoutSyndrome and work satisfaction among Nursing Professionals. There is a moderate level of satisfactiondue mainly because of intrinsic factors at work. The socio demographic variables have a low effect on thesyndrome dimensions.